A lightweight liquid cooling thermal management structure for prismatic batteries. (October 2021) - Tang, Zhiguo; Liu, Zhiqing; Li, Jie; Cheng, Jianping
Highlights: A lightweight liquid cooling BTMS was proposed for prismatic batteries. Cooling structure was optimized for battery module containing four batteries. The BTMS weight ratios of D22 and D24 were only 1.88% and 2.36%. Abstract: Limited by the small space size of electric vehicles (EVs), more concise and lightweight battery thermal management system (BTMS) is in great demand. In current study, a novel liquid cooling structure with ultra-thin cooling plates and a slender tube for prismatic batteries was developed to meet the BTMS requirements and make the BTMS lighter. Three-dimensional transient simulations were conducted on the proposed battery module, and the two-pair battery is selected as the research object based on the preliminary analysis of several battery pairs, with a further four structural designs proposed for the optimization analysis. Then the effects of the cooling structure, coolant inlet velocity ( v ), battery discharge rate and tube inner diameter ( d ) on the cooling performance were investigated by numerical simulation. Results demonstrate the superior cooling effect of two designs among several cooling structures. For the first, the length of the cooling tube in contact with each pair of batteries increases along the coolant flow direction, and v and d of 0.25 m/s and 2.5 mm is able to reduce the maximum temperature of the batteries ( T max ) to 38.28°C and temperature difference in the battery module ( Δ T max ) to 4.23°C, respectively. For the second, the cooling tube is evenly distributed to each pair of batteries, and a higher mass flow improves the cooling effect, and the structure with v and d of 0.5 m/s and 2 mm is able to reduce T max and Δ T max to 34.97 and 4.04°C. Furthermore, the BTMS weight ratios of these two designs are just determined as 1.88% and 2.00%, respectively.